Breaking the Bubble: Bullous scabies – A case report - Safi Ur Rehman Daim; Muhammad Fawad Ashraf; Aizaz Ashraf; Rameesha Zubair; Rana Uzair Ahmed (IDCases, 2023)
The article describes a rare case of bullous scabies in a 30-year-old female. Scabies is a skin condition caused by the mite Sarcoptes scabiei and is typically transmitted through skin-to-skin contact. Bullous scabies is a rare presentation of scabies and is characterized by tense bullae and blisters that resemble bullous pemphigoid. The patient presented with pruritus, bullae on the hands and feet, and papules on various body parts. After a provisional diagnosis of scabies was made, microscopic examination confirmed the presence of mites and eggs. The patient was treated with Permethrin cream and antihistamines, and her symptoms regressed over the next two months. The husband and two other family members also reported improvement after treatment. While bullous scabies is an uncommon presentation of scabies, it is important to consider it in the differential diagnosis for patients presenting with bullae and pruritus. The exact pathophysiology of bullous scabies is yet to be determined, but theories include a staph aureus superinfection or production of autoantibodies in response to scabies lytic enzymes. Early recognition and appropriate treatment can lead to good outcomes in patients with bullous scabies.